RESPONS TANAMAN PADI ORGANIK (Oryza sativa L.) TERHADAP BAKTERI PELARUT FOSFAT (BPF) DAN MIKORIZA VESIKULAR ARBUSKULAR (MVA) - Suryaman Birnadi (JURNAL ISTEK, 2012)
An experiment was conducted to study growth and yield of organic rice with BPF and MVA. The experiment was carried out at field Sindangreret, Cileunyi , Bandung, from july 2010 up to November 2010. Randomized block design with factorial pattern was used with three replications to study effect complete combinations BPF at three levels (b0 = 0 BPF, b1 = Pseudomonas diminuta, dan b2 = Pseudomonas cerevisiae ) with four levels MVA (m0 = 0 MVA, m2 = 10 t/ha, m3 = 15 t/ha dan m4 = 20 t/ha). Result showed there are no interaction effect between the application of BPF and MVA. Although there is significant effect an main effect of growth and yield. BPF proveed to be the highest effect on plant height, or number vegetative, dry plant weight, weight of dry harvest grain rice NPK absorption, and the mean growth rate. MVA proveed to be the highest effect on plant height, on number vegetative, dry plant weight, proved to be the highest effect an weight of dry harvest grain rice.